Coinfection with chikungunya and Zika results in mild disease and distinct inflammatory response - Juliana Cardoso Alves; Lucas Sousa Magalhães; Priscila Lima dos Santos; Regina Adalva de Lucena Couto Ócea; Alejandra Debbo; Jaira Vanessa de Carvalho; Mauro Martins Teixeira; Suresh Mahalingam; Amelia Ribeiro de Jesus; Angela Maria da Silva; Roque Pacheco de Almeida; Camilla Natália Oliveira Santos (npj Viruses)
Abstract Chikungunya (CHIKV) and Zika (ZIKV) viruses, both mosquito-borne, often circulate simultaneously, raising concerns about the effects of coinfection. This study evaluated cytokines, chemokines, and growth factors in 12 patients with concurrent CHIKV and ZIKV infections confirmed by RT-qPCR. Clinical data and 45 immune mediators were analyzed. Coinfected and monoinfected patients exhibited similar symptoms, although ZIKV-infected individuals experienced fewer instances of fever. No patients had persistent symptoms or required hospitalization. Chemokines CCL5, CXCL1, and CXCL10 were elevated across all groups. CHIKV-infected patients showed higher levels of CCL2, CCL4, EGF, CXCL12, and IFN-α compared to controls, while IL-1RA, IL-8, and IFN-γ were elevated in both CHIKV and coinfected groups. SCF was elevated only in the ZIKV group. Overall, CHIKV and ZIKV coinfection presented mild clinical symptoms similar to monoinfections and demonstrated a moderate inflammatory response.